Odpowiedź :
Odpowiedź:
[tex]\left(\dfrac{6\sqrt[3]{3}}{2^2}\right)^3=\left(\dfrac{\not6^3\sqrt[3]{3}}{\not4_{2} }\right)^2=\left(\dfrac{3\sqrt[3]{3}}{2}\right)^2=\dfrac{3^3*(\sqrt[3]{3})^3}{2^3}=\dfrac{27*3}{8}=\dfrac{81}{8}=10\dfrac{1}{8}[/tex]
Cześć!
Szczegółowe wyjaśnienie:
i)
[tex] (\frac{6 \sqrt[3]{3} }{2 {}^{2} } ) {}^{3} = ( \frac{3 {}^{3} \cdot2 {}^{3} \sqrt{3} }{2 {}^{2} } ) {}^{3} =( 3 {}^{ 3} \cdot2 \sqrt{3} ) {}^{3} =( 27 \cdot2 {}^{} \sqrt{3} ) {}^{3} = (54 \sqrt{3}) {}^{3} = 54 {}^{3} \cdot3 \sqrt{3} = 3 \cdot54 {}^{3} \sqrt{3} [/tex]